Microvascular Loss and Diastolic Dysfunction in Severe Symptomatic Cardiac Allograft Vasculopathy. (August 2018) - Daud, Anees; Xu, David; Revelo, Monica P.; Shah, Zubair; Drakos, Stavros G.; Dranow, Elizabeth; Stoddard, Gregory; Kfoury, Abdallah G.; Hammond, M. Elizabeth H.; Nativi-Nicolau, Jose; Alharethi, Rami; Miller, Dylan V.; et al.
Abstract : Background: Cardiac allograft vasculopathy (CAV) remains an important source of mortality after heart transplant. The aim of our study was to identify structural and microvasculature changes in severe CAV. Methods and Results: The study group included heart transplant recipients with severe CAV who underwent retransplantation (severe CAV, n=20). Control groups included time from transplant matched cardiac transplant recipients without CAV (transplant control, n=20), severe ischemic cardiomyopathy patients requiring left ventricular assist device implantation (ischemic control, n=18), and normal hearts donated for research (donor control, n=10). We collected baseline demographic information, echocardiography data, and performed histopathologic examination of myocardial microvasculature. Echocardiographic features of severe CAV included lack of eccentric remodeling and presence of significant diastolic dysfunction. In contrast, diastolic function was preserved in transplant control subjects. Histopathologic examination showed increased interstitial fibrosis among severe CAV, transplant controls, and ischemic control patients. Compared with transplant controls, severe CAV subjects had reduced capillary density and increased capillary wall thickness ( P <0.05). Conclusions: Our results suggest that the marked diastolic dysfunction and resultant symptoms in patients with severe CAV may be secondary to the loss of microvasculature and remodeling of remaining microvessels rather than a consequence of interstitial fibrosis. The clinical significance and potential therapeutic implications of these unique microvasculature characteristics warrant further investigation. Abstract : Supplemental Digital Content is available in the text.